WHAT DOES THE DMK’S 2021 ELECTION CAMPAIGN SONG FOCUS ON? : A MULTIMODAL DISCOURSE ANALYSIS - Neelambari, G V (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Methods to convince voters are continuously evolving since the inception of elections. Contesting political parties have used every possible media from posters to short videos to approach and impress voters. With creativity paving ways to innovative campaign strategy and methods, studies focusing on them are gaining momentum. Campaign songs play an engaging role in this campaign communication strategy in the state of Tamil Nadu. Initially, campaign songs were written to create awareness of parties’ name, symbol, and ideology among the illiterate population. With time, the focus of the songs has shifted to party leaders. The 2021 Tamil Nadu election witnessed the release of campaign songs by state and national political parties. Thanks to social media, these songs had massive reach on social networking sites among people of all age groups. In this context, this paper aims to analyze the official campaign song released by the state political party DMK for the 2021 Tamil Nadu election based on the multimodal discourse analysis informed by Visual grammar.